2014
DOI: 10.1111/jfpe.12113
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Defective (Full Black, Full Sour and Immature) and Nondefective Coffee Beans by Their Physical Properties

Abstract: In this research the physical properties of defective and nondefective coffee beans were investigated. The study results show that there are highly significant differences (P < 0.001) in the physical properties (true and bulk volume, true and bulk density, mass) and (P < 0.05) in sphericity and porosity of green coffee beans, respectively. Higher and lower values of mass and dimensional parameters were obtained in full sour and full black coffee beans, respectively. On the other hand, the physical properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
5
0
4
Order By: Relevance
“…The coffee beans tend to the spherical shape by increasing moisture, causing a slight increase in the sphericity (Equation 6), as shown in Figure (between 0.827 ± 0.009 and 0.842 ± 0.007). The operational sphericity (Mohsenin, ; Wadell, ) of the coffee beans (Equation 3) were between 0.695 ± 0.009 and 0.732 ± 0.007, which approximate to the values obtained for the coffee bean by other researchers (Afonso Júnior et al, ; Belay et al, ; Dias, ; Yuwana, Silvia, & Sidebang, ). The effect of moisture on the dimensions and on sphericity of coffee beans were best described by the power law model (Equation 13; coefficients on Table ).…”
Section: Resultssupporting
confidence: 77%
“…The coffee beans tend to the spherical shape by increasing moisture, causing a slight increase in the sphericity (Equation 6), as shown in Figure (between 0.827 ± 0.009 and 0.842 ± 0.007). The operational sphericity (Mohsenin, ; Wadell, ) of the coffee beans (Equation 3) were between 0.695 ± 0.009 and 0.732 ± 0.007, which approximate to the values obtained for the coffee bean by other researchers (Afonso Júnior et al, ; Belay et al, ; Dias, ; Yuwana, Silvia, & Sidebang, ). The effect of moisture on the dimensions and on sphericity of coffee beans were best described by the power law model (Equation 13; coefficients on Table ).…”
Section: Resultssupporting
confidence: 77%
“…Currently, it represents 20% of the total coffee produced in Brazil (Mazzafera, 1999; Ramalakshmi, Kubra, & Rao, 2007). In Ethiopia, the percentage of defected beans are higher than other countries (Belay et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These studies are shown that there is difference in the physical and chemical properties between immature, black, sour, and nondefective coffee beans. Recent study showed the physical property alone can successfully separate defective and nondefective beans (Belay et al., 2014). Other studies (Mendonça, Franca, & Oliveira, 2009) also applied sieving for separation of these beans.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the defective bean removal is a critical stage that affects the bean's value, as many experts explicitly point out that defective beans are a key factor for providing high-quality coffee. Thus, removing defective beans becomes a necessary step before brewing for significantly increasing their competition and profits [2]. The SCAA has classified the defective beans into 13 classes [3], as shown in upper portion of Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The SCAA has classified the defective beans into 13 classes [3], as shown in upper portion of Figure 1. Most popular defective bean removal processes are achieved by manual or mechanical manners in the past decades [1,2,4,5]. Nevertheless, these solutions focus on removing few sorts of defects in the SCAA's classification.…”
Section: Introductionmentioning
confidence: 99%